Organizational Innovation Behavior in Taiwan’s University Libraries: A Quantitative Study - Chen Su-May Sheih (Jiàoyù zīliào yǔ túshūguǎn xué, 2015)
In this study, the researcher deployed questionnaire to understand the status quo and factors of organizational innovation behavior of Taiwan’s university libraries. The respondents were 785 librarians served in 144 university libraries. Study results revealed, first, the majority of respondents confirmed organizational innovation in their libraries. Among the innovative events or behaviors, more technical innovations were identified than management innovations were. Second, organizational climate was identified having positive relation to organizational innovations. Third, in terms of organizational structure, the formalization of library universities was positively recognized. Finally, the results suggested that formalization of organization, support of managers, encouragement of organization, and resources and in-service education had significant influence on innovative behaviors. However, the participation in decision making had negative relation to innovational behaviors.